2010
DOI: 10.1590/s0100-06832010000500027
|View full text |Cite
|
Sign up to set email alerts
|

Disponibilidade de potássio para as plantas em solos do sul do Brasil estimada por métodos multielementares

Abstract: RESUMOA avaliação da disponibilidade de K para as plantas é feita pela estimativa de seus teores na forma trocável. Métodos multielementares aumentam a eficiência nos laboratórios de análises de solo, porém a capacidade de troca de cátions (CTC) do solo pode alterar a predição do K disponível. O objetivo deste trabalho foi estimar o K disponível para o milho e para a soja em solos representativos do Estado do RS, pelos métodos Mehlich-1 (M 1 ), Mehlich-3 (M 3 ), resina de troca iônica (resina) e Acetato de Amô… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 10 publications
6
4
0
1
Order By: Relevance
“…The slope of the regression, however, differed significantly from "1", at both times of shaking, possibly due to some systematic difference. However, for the 60-min shaking time, the "a" (intercept) and "b" (slope) values were not different from "0" and "1", respectively (Table 2, also as shown in Figure 1F), indicating that the two solutions extract equivalent amounts of exchangeable K. Similar results are reported in the literature by several authors (Shuman and Duncan 1990; Boeira et al 2004;Bortolon et al 2010). …”
Section: Potassiumsupporting
confidence: 86%
See 2 more Smart Citations
“…The slope of the regression, however, differed significantly from "1", at both times of shaking, possibly due to some systematic difference. However, for the 60-min shaking time, the "a" (intercept) and "b" (slope) values were not different from "0" and "1", respectively (Table 2, also as shown in Figure 1F), indicating that the two solutions extract equivalent amounts of exchangeable K. Similar results are reported in the literature by several authors (Shuman and Duncan 1990; Boeira et al 2004;Bortolon et al 2010). …”
Section: Potassiumsupporting
confidence: 86%
“…Despite the high correlation coefficient (r=0.95), it is evident that Mehlich-1 extracts smaller amounts of K compared to standard 1.0 M NH 4 OAc, mainly in soils with high level of K. Similar amounts of K, however, were extracted up to 0.30 cmol c kg -1(Figures 1A, 1B and 1C). These results are in agreement with those of several other studies(Zbíral and Nemec 2005;Hosseinpur and Samavati 2008;Bortolon et al 2010). It can be speculated that the higher extraction capacity of NH 4 OAc is due to the ability of the NH 4 + to replace K in the 2:1 mineral interlayer.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Slaton et al (2010) compared Mehlich-3 and 1 mol L -1 HNO 3 and found that Mehlich-3-extractable K is an excellent predictor of soil K availability for soybean grown on silt loams in eastern Arkansas. Bortolon et al (2010) found that Mehlich-1, Mehlich-3, and ion exchange resin extractants were good indices for available K estimation for soybean and wheat in soils of southern Brazil. On the other hand, Hosseinpur and Zarenia (2012) showed that 1 mol L -1 NH4OAc, 0.1 mol L -1 BaCl 2 , 0.1 mol L -1 HCl, and boiling 1 mol L -1 HNO 3 can not be used as available K extractants, whereas 0.1 mol L -1 HNO 3 , Mehlich-1, and 0.01 mol L -1 CaCl 2 extractants would be suitable as soil testing methods for determining available K for common bean in Iran soils.…”
Section: Introductionmentioning
confidence: 93%
“…However, available K to plants is controlled by a complex exchange phenomenon between the solid and solution phases (Martin and Sparks, 1985). The most commonly used methods for estimating the content of available K for plants are those that determine exchangeable K, such as the ammonium acetate (NH 4 OAc 1 mol L -1 ), Mehlich-1 (HCl 0.05 mol L -1 + H 2 SO 4 0.0125 mol L -1 ) and cation exchange resin methods (Bortolon et al, 2010). However, assessing the exchangeable K form alone is not sufficient for estimating the total K uptake by crops, because some non-exchangeable K can be released from K-bearing clay minerals (Meurer and Anghinoni, 1993;Bortoluzzi et al, 2005;Darunsontaya et al, 2012;Moterle et al, 2016).…”
Section: Introductionmentioning
confidence: 99%